A Retrospective Study on Acute Poisoning Cases in Tertiary Care Centers of Western Nepal - Karna, Priya; Thakur, Amit Kumar; Parajuli, Sudhir Raman; Subedi, Ashmin (Annapurna Journal of Health Sciences, 2025)
Introduction: Poisoning is a major public health problem and a reason for significant morbidity and mortality worldwide. It is one of the most common presentations in an emergency department. This study was carried out to evaluate the pattern of acute poisoning cases in attending emergency room of Manipal Teaching Hospital. Methods: This is a retrospective observational study done by manually going through and analyzing all the files of 83 cases of acute poisoning attending the emergency department of Manipal Teaching Hospital during the period of 1st Jan 2020 - 30th Dec 2021. Results: Out of all 83 cases, the maximum percentage (58.33%) of poisoning occurred in females of the younger age group. Maximum number of cases attending was during January (18.07%) during weekdays i.e., on Monday (20.48%). Most of the cases attended with organophosphorus poisoning (37.34%) for deliberate self-harm. A majority of patients (79.51%) presented with nausea and vomiting (72.28%) followed by abdominal pain (15.66%). The overall treatment outcome was good with (75.90%) were discharged following proper management and care. Conclusion: The maximum cases of acute poisoning attending the emergency department were younger females of 15-25 years of age. Males of age 25-35 years of age were found to be most affected. There is a steep rise in cases in males of the age group >55 years. Organophosphorus compounds were used in most of the case